Belt and Road Initiative in Africa: The Impact of Standard Gauge Railway in Kenya. (August 2019) - Githaiga, Nancy Muthoni; Bing, Wang
China's Belt and Road has been billed as the single most significant undertaking by the country on the international stage. In Africa, Kenya is a core part of both the Maritime Silk Road and the Belt. The authors have examined the flagship project of this initiative in Kenya, the Standard Gauge Railway (SGR) from the port of Mombasa to Nairobi, with a view to analyse the impact so far. Issues of employment, debt sustainability, neocolonialism and specific aspects of the project were looked at. Although our findings indicate that the SGR so far has both positive aspects as well as challenges, for the project to be successful both China and Kenya need to create a synergy towards solving concerns that have arisen from the completion of phase 1 of the project.